The Peruvian Central Sierra (1821-1870) an Andean Regional Economy - Burga, Manuel (1983)
The Municipality of Tarma, at the end of the 18th century, corresponded almost entirely to what is considered the central region. After Independence, in 1825, this administration took the name of the department of Junín and the provinces of Tarma, Jauja, Huancayo and Cerro de Pasco were assigned to it. This same political demarcation will remain unchanged in this department during the period that interests us.